Los fantasmas del comunismo y Marx en Chile en la década de 1870 - Ortega Martínez, Luis (Revista de Historia Social y de las Mentalidades, 2011)
The rise and tragic fall of the Paris Commune were reported extensively by the press of Valparaíso and Santiago. What the newspapers did was not just the result of the interest about a distant although dramatic event, but a biased coverage that was related to the transformations that Chile had been experiencing from the early 1850s which as one important byproduct had turned up an increasing number of salaried workers. Whether in the constructions and operation of the railways and other public works or in the new factories that sprung up in the main cities, or in the coal mining districts, an everincreasing number of proletarians were becoming part of Chile’s social life. The news about the Paris Commune in the Chilean press was a warning at a very early stage of the formation of the «world of labour» in the country. In the hitherto calm horizon the spectres of Communism and Karl Marx had already emerged.